Trabalho docente e ferramentas digitais: reflexões sobre a formação de professores à luz do interacionismo sociodiscursivo e da clínica da atividade - Albuquerque, Francisca Geane de (2021)
The use and appropriation of digital artifacts are part of the teaching work, constituting a complex process. In this sense, we can state that knowing how to use and explore digital tools in their full potential necessarily involves the teacher's digital literacy and a process of instrumental genesis (RABARDEL, 1995). Considering the importance of this theme for the initial training of teachers, the interest in conducting this research, which is qualitative in nature, emerged (DENZIN; LINCOLN, 2006), and it aims to investigate how a professor understands her teaching activity based on the use of digital artifacts in an instrumental genesis process. More specifically, the study aims to: 1) investigate how the professor understands her way of acting with digital tools; 2) analyze the knowledge that the professor mobilizes to appropriate technological artifacts; 3) identify how students are represented in the professor's texts at the time of appropriation and use of digital tools in the classroom. We adopted the Sociodiscursive Interactionism theoretical methodological framework - ISD - (BRONCKART 1999, 2006, 2008), in dialogue with the Clinic of Activity (CLOT, 2007, 2010; CLOT; FAÏTA, 2000), Ergonomics of Activity (AMIGUES, 2004; SAUJAT, 2004) and the Instrumental Genesis (RABARDEL, 1995), as references for the analysis of our corpus. The data were generated through a simple self-confrontation session (CLOT; FAÏTA 2001; VIEIRA; FAÏTA, 2003) carried out with the professor who collaborated with the research. The analysis of the data generated in the self-confrontation was carried out based on the textual analysis framework proposed by the ISD, considering the context of production and the enunciative level, materialized through the voices, modalizations and person index in the teacher's texts-discourses. The result of the analysis revealed that the professor understands the genesis of artifacts in the teaching context itself, transforming them into instruments in the course of action, together with her students. On the construction of knowledge for/in instrumental genesis, the texts revealed evidence of the agent-teacher's social world, regulated by institutionalized prescriptions by educational instances. The professor resorts to the academic world to have access to acting models, with prescriptions arising from the experience in distance learning, where the digital instruments that mediate the teaching action stand out. The theme of this work is relevant when it discusses how foreign language degree courses understand and deal with the process of instrumental genesis. In addition, it seeks to contribute to the understanding of the teaching activity in the various aspects that make up this métier.